The synthesis, characterisation and photophysical properties of novel tri-substituted-8-azafluoranthene compounds and their Cu(1) complexes - Nordon, Amy Theresa (Trinity College (Dublin, Ireland). School of Chemistry, 2012)
Chapter 1: This chapter details the synthesis and charaeterisation of a family of novel tri-substituted-8-azafluoranthene eompounds that have N^N bidentate ligand capabilities. The compounds are synthesised via a Diels-Alder cycloaddition and two methods of synthesis are employed; a conventional method using a sand bath to heat the reaction and a microwave assisted method. The methods are compared for efficiency. The resulting six compounds; 7,10-diphenyl-9-(2-pyridyl)-8- azafluoranthene (6), 7,10-diphenyl-9-(6-methyl-2-pyridyl)-8-azafluoranthene (7), 7,10- diphenyl-9-(6-cyano-2-pyridyl)-8-azafluoranthene (8), 7,10-di(4-tert-butylphenyl)-9- (2-pyridyl)-8-azafluoranthene (9), 7,10-di[(4-trifluoromethyl)phenyl]-9-(2-pyridyl)-8- azafluoranthene (10) and 7,10-di(4-tert-butylphenyl)-9-(6-cyano-2-pyridyl)-8- azafluoranthene (13) are fully characterised by NMR and mass spectrometry.
Keywords: Chemistry, Ph.D.; Ph.D. Trinity College Dublin.